THE INFLUENCE OF PRODUCT VARIETY AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION - Sri Lestari; Leonard Adrie Manafe (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The abundance of traders who sell various kinds of light snacks at very affordable prices, makes competition in the world of trade more intense thus sales increase more rapidly. For this reason, basreng (